2020
DOI: 10.1039/d0an00174k
|View full text |Cite
|
Sign up to set email alerts
|

A high-throughput SAMDI-mass spectrometry assay for isocitrate dehydrogenase 1

Abstract: This paper reports a SAMDI-mass spectrometry assay that can evaluate antagonists of cancer-associated isocitrate dehydrogenase 1 in high throughput.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Second, there remains a need for high-throughput and robust screening assays suitable for identifying ligand–target interactions. Here we expand the capabilities of the SAMDI technology, extensively reported as a powerful label-free and high-throughput assay for measuring biochemical and chemical reactions, 9,1828 to offer a high-throughput ASMS assay with key benefits over traditional ASMS approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Second, there remains a need for high-throughput and robust screening assays suitable for identifying ligand–target interactions. Here we expand the capabilities of the SAMDI technology, extensively reported as a powerful label-free and high-throughput assay for measuring biochemical and chemical reactions, 9,1828 to offer a high-throughput ASMS assay with key benefits over traditional ASMS approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent reports have further demonstrated the applicability of SAMDI to a variety of cellular assay formats, including monitoring of PTP activity in HeLa cells cultured directly on SAMDI plates, 85,86 PTP activity in lysates from five different mammalian cell lines, 87 and isocitrate dehydrogenase 1 activity in lysates from LN382 cells. 88…”
Section: Samdi-msmentioning
confidence: 99%
“…These developments have revolutionized the HTA space because AIMS techniques enable throughputs that are orders of magnitude higher than those of conventional LC‐MS tools, approaching analysis rates that are achievable with fluorescence‐based techniques but without the need for fluorescent labels. Several surface‐based MS techniques, such as matrix‐assisted laser desorption/ionization (MALDI), direct analysis in real‐time (DART), desorption electrospray ionization (DESI), secondary ion mass spectrometry (SIMS), and self‐assembled monolayers coupled with desorption/ionization (SAMDI), are capable of direct ionization of analytes with little to no sample preparation and have been demonstrated to be applicable in situations that require short analysis times and very small sample volumes 79,80 . An in‐depth review of the many AIMS approaches that have been reported thus far has been written by Kuo et al 81 .…”
Section: Mass Spectrometrymentioning
confidence: 99%